ANALISIS PENGARUH PENDIDIKAN DAN PEKERJAAN TERHADAP PENGETAHUAN PRODUK PERBANKAN SYARI’AH (Studi Kasus Kepala Keluarga di Dukuh Krapyak Kulon, Panggungharjo, Sewon, Bantul, Yogyakarta Tahun 2013) Musyaﬁ q Hasyim dan Abdullah Salam - Musyafiq Hasyim; Abdullah Salam (Universitas Alma Ata, 2015)
Abstract This study aims to determine the effect of education (educational status) and employment (job status) to the knowledge of shari’ah banking products households in Padukuhan/Krapyak Dukuh Kulon, Panggungharjo, Sewon, Bantul, Yogyakarta. sThe population in this study was 917 heads of families that are recorded in card family in Padukuhan/Dukuh Kulon Krapyak Panggungharjo, Sewon, Bantul, Yogyakarta. The sample in this study is taken by the method 10-15% of the population and should not be less than 10% of total sample of 95 respondents. Results of t test analysis shows that each of the independent variables signiﬁ cantly inﬂ uence the knowledge of banking products shari’ah. In the F test showed that the independent variables have a signiﬁ cant effect. The determinansi coefﬁ cient (R²) of 0.173, which means knowledge of banking products shari’ah in Padukuhan Krapyak Kulon able to be explained by the independent variables of 17.3% and the remaining 82.7% is inﬂ uenced by other variables outside of this research model. Keyword: Education, Job Status, The Knowledge of Syari’ah Banking Product